Effect of Phytase on the Sodium Requirement of Starting Broilers 1. Sodium Bicarbonate as Primary Sodium Source - Goodgame, S.D.; Mussini, F.J.; Lu, C.; Bradley, C.D.; Waldroup, P.W. (International Journal of Poultry Science, 2011)
Recent work has indicated that phytase enzymes may influence Sodium (Na) metabolism in the chick but to date no work has conclusively demonstrated that the Na requirement of the chick for live performance is influenced by phytase supplementation. In this study male broilers were fed diets with Na levels ranging from 0.10-0.28% using sodium bicarbonate as the primary source of supplemental Na. Diets were supplemented with no phytase, 500 FTU/kg (1x) or 2,000 FTU/kg (4x) of phytase. When phytase was added the dietary Ca and Nonphytate P (NPP) were adjusted in accordance with anticipated release of these minerals. For 1x phytase the Ca and NPP were reduced 0.10% each and for 4x phytase were reduced by 0.20% each. The combination of seven Na levels and three phytase treatments resulted in 21 dietary treatments, each of which was fed to six replicate pens of five male chicks housed in electrically heated battery brooders with wire floors. Experimental diets and tap water were provided for ad libitum consumption from day of hatch to 18 d. At 16 d of age excreta from each pen was collected and freeze dried to determine moisture content and the excreta analyzed to determine amounts of Ca, P and Na. There were no significant differences in Body Weight (BW), Feed Conversion (FCR), Feed Intake (FI), fecal moisture (FH2O), or mortality of broilers fed diets with different levels of phytase indicating that the dietary adjustment in NPP and Ca levels for the addition of the phytase did not adversely affect performance of the birds. The dietary Na level significantly affected BW, FCR, FI or FH2O. There were no significant interactions of dietary Na and level of phytase supplementation. Regression analysis showed an overall estimate of 0.18±0.01% Na for BW and 0.19±0.01% Na for FCR. There was little indication that the Na requirement was affected by phytase. The level of phytase and Na in the diet had significant effects on excreta levels of P, Ca and Na. The use of lower dietary levels of NPP and Ca in association with the addition of the phytase resulted in significant reduction in excreta levels of these minerals, but had no significant effect on levels of excreted Na. Increasing the dietary Na level significantly affected the levels of all three minerals in the excreta. Although the dietary Na level had significant effects on both excreta P and Ca, these followed no consistent trends with no significant difference in Ca or P excretion between chicks fed diets with the lowest and highest Na levels. There were significant interactions between dietary Na levels and levels of phytase supplementation for all three minerals in the excreta. However, these did not appear to follow any consistent pattern. While it is apparent that phytase influences the metabolism of Na within the body, the data from the present study suggests that this has little impact on the dietary need for Na.